Re-imagining the Teaching of European History Promoting Civic Education and Historical Consciousness - Gómez, Cosme (Taylor & Francis, 2023)
This book explores the challenges of teaching European history in the 21st century and provides research-informed approaches to history teaching that combine civic education, historical consciousness, and the teaching of controversial social issues. With contributions from researchers across Europe, the book includes both theoretical and case study chapters. The first part of the book addresses issues such as globalization and teaching in an interconnected world, using multicultural and critical approaches, decolonizing education, and teaching uncomfortable narratives of the past. The second part of the book showcases thematic chapters dedicated to teaching intersecting topics in the European curriculum such as violence and armed conflict, social inequality, gender equality, the technological revolution, and religion. Ultimately, this volume promotes criticality, civic engagement, and reflection on social issues, thereby prompting methodological change in the teaching of history as we know it. It will appeal to researchers and students of history education, democratic education, and citizenship education, as well as teacher educators and trainee teachers in history.